O exercício físico como instrumento convencional no tratamento e prevenção da doença de Parkinson - Ricardo Sant'Anna Alves Barroso (2020)
This work aimed to discuss the role of physical exercise for individuals affected by Parkinson's disease, in order to resize the approach taken so far by the scientific community and by professionals who work with this audience. This study had two objectives 1) to present evidence that physical exercise should be seen as a conventional instrument for the prevention and treatment of Parkinson's disease; 2) present a 12-week multicomponent training protocol exclusively for individuals with Parkinson's. In the first part of the work, a bibliographic review was carried out in order to support the theory that physical exercise should be a conventional treatment, in addition to this, it should be the first treatment made available to patients since it provides benefits in motor and non-motor symptoms, in the quality of life and has an important role in protecting parkinson's as it generates neuroprotection and does not produce any adverse side effect. In the second part we present a multicomponent training protocol that aimed to positively impact the levels of physical fitness, physical activity and quality of life of patients. It was possible to observe, through the records in the field diaries of the researchers / observers and participants of the physical exercise sessions, the evolution of the classes and of the participants and the positive changes that the protocol was able to generate for those who participated in the + VidaParkinson project.